2002
DOI: 10.1111/j.1365-2621.2002.tb08877.x
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Measurement of Oxygen in Modified Atmosphere Packaged Hams Using a Phase‐Fluorimetric Sensor System

Abstract: The phase-fluorimetric oxygen sensing system recently developed by our team was used for nondestructive measurement of oxygen content in the heasdspace of 4 types of ham slice products. The system allowed accurate measurement of oxygen levels in all types of ham packs in a contact-less nondestructive fashion; it worked satisfactorily under ambient light and in conditions of direct contact with packaged cooked ham slices and variation of sample temperature. A primary screening for oxygen content of the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…The results of the screening of batches of commercial cheese products containing the oxygen sensor stickers and packaged under modified atmosphere packaging line correlate well with previous similar studies conducted by our research team but involving different food types (Fitzgerald et al, 2001;OÕMahony et al, 2004;Papkovsky et al, 2002;Smiddy, Fitzgerald et al, 2002;Smiddy, Papkovskaia et al, 2002). A substantial fraction of commercial packaged food products (5% in this trial) were found to be susceptible to oxygen leaks due to accidental package damage to the corners of the thermoformed packs during packaging, handling and transportation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of the screening of batches of commercial cheese products containing the oxygen sensor stickers and packaged under modified atmosphere packaging line correlate well with previous similar studies conducted by our research team but involving different food types (Fitzgerald et al, 2001;OÕMahony et al, 2004;Papkovsky et al, 2002;Smiddy, Fitzgerald et al, 2002;Smiddy, Papkovskaia et al, 2002). A substantial fraction of commercial packaged food products (5% in this trial) were found to be susceptible to oxygen leaks due to accidental package damage to the corners of the thermoformed packs during packaging, handling and transportation.…”
Section: Discussionsupporting
confidence: 86%
“…The sensors were calibrated as described elsewhere earlier (OÕMahony et al, 2004;Papkovsky et al, 2002). Only one sensor from the batch was calibrated with a set of standard gas mixtures 0.00%, 0.504%, 1.93%, 5.00%, 9.84%, 20.5%, 100% oxygen balanced with nitrogen (BOC, Dublin, Ireland) at +4°C.…”
Section: Oxygen Sensors and Measurement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of molecular oxygen in the packaging headspace influences into the sensitive coating by simple diffusion and quenches luminescence in a dynamic fashion. The concentration of oxygen is then estimated based on the degree of alteration in luminescence parameters, using a predetermined calibration (Papkovsky et al 2002). The process is reversible and clean, and there is no consumption of either dye or oxygen in the photochemical reactions involved, as well as no generation of byproducts.…”
Section: Fluorescence-base Oxygen Sensorsmentioning
confidence: 99%
“…These studies further demonstrated the suitability of such sensors for measuring oxygen levels in commercially used meat packaging and their potential as predictors of quality. Papkovsky et al (2002) used oxygen sensors to measure oxygen content in the headspace of four commercial sliced ham products. Accurate measurements were made under ambient light conditions, in direct contact with the product and under conditions of significant temperature variation.…”
Section: Fluorescence-based Oxygen Sensorsmentioning
confidence: 99%